Sociology of patients’ rights: selected remarks, analysis and reflection - Kmieciak, Błażej (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The legal situation of the patient has become one of the most important elements of the debate on health care. It is related to the specific situation. The patient during a meeting with a medical expert is forced to provide intimate details about his life. Patients’ rights are most often analysed in legal terms relating to specific laws or regulations. It should be noted, however, that these rights of patients “live” primarily in institutions such as hospitals or clinics. Moreover, they are not only a part of the broadly understood system of medical law. They refer to a specific meeting that occurs between the patient and the medical expert. How can the mentioned relationship be applied to the concept of patients’ rights? Are there any laws that specifically relate to the interaction which occurs between the doctor and the patient? Is the formal implementation of the regulations sufficient to conclude that patients’ rights are fully respected? The proposed article is an attempt to answer these questions.